Rancangan Monitoring Lalu Lintas Pedesaan menggunakan Metode Background Subtraction - Sanjaya, Tedy; Siregar, Rosyidah (Explorer, 2025)
Vehicle monitoring in rural tourist areas is an essential aspect of traffic management and safety. Video-based monitoring systems can be an effective solution for detecting and counting passing vehicles. This study proposes the use of the Background Subtraction method to detect objects, particularly vehicles, in monitoring videos recorded in tourist areas. This method utilizes the difference between the background and moving objects to identify passing vehicles, enabling automated monitoring without manual intervention. A comparison between manual counting and the automated system on five test videos showed perfect consistency, with no discrepancies in the detected number of vehicles. In a 5-second video, the system detected 4 vehicles, matching the manual count. A 6-second video recorded 2 and 1 vehicles, with identical results between the system and manual calculations. Videos lasting 11 minutes and 18 seconds each recorded 2 vehicles, with no difference between the two counting methods. The use of the Background Subtraction method achieves high detection accuracy in counting vehicles entering tourist areas, even under varying lighting conditions and environmental disturbances. This confirms that the Background Subtraction method is effective for traffic monitoring in rural areas and can be successfully applied to manage traffic in such regions.